2022
DOI: 10.3390/nano12173026
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Ferroelectric Materials-Based Photoelectrochemical Reaction

Abstract: Inorganic perovskite ferroelectric-based nanomaterials as sustainable new energy materials, due to their intrinsic ferroelectricity and environmental compatibility, are intended to play a crucial role in photoelectrochemical field as major functional materials. Because of versatile physical properties and excellent optoelectronic properties, ferroelectric-based nanomaterials attract much attention in the field of photocatalysis, photoelectrochemical water splitting and photovoltaic. The aim of this review is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…It has been shown that an internal field due to a polar crystal structure (e.g., in ferroelectrics) minimizes charge carrier recombination and instead favors transfer at the interfaces. 57 Both CaFeSeO and CaFeSO samples studied in this work adopt polar crystal structures (of Cmc2 1 and P6 3 mc symmetries, respectively) 18,25 and are composed of polar units (FeO 2 Se 2 and FeOS 3 pseudotetrahedra), in contrast to the centrosymmetric, nonpolar structures of La 2 O 2 Fe 2 OQ 2 (I4/mmm symmetry) with slower kinetics. It is not clear whether a dipole across the photoactive cation or a polar axis in the crystal structure would have the greater effect of enhancing e − −h + separation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been shown that an internal field due to a polar crystal structure (e.g., in ferroelectrics) minimizes charge carrier recombination and instead favors transfer at the interfaces. 57 Both CaFeSeO and CaFeSO samples studied in this work adopt polar crystal structures (of Cmc2 1 and P6 3 mc symmetries, respectively) 18,25 and are composed of polar units (FeO 2 Se 2 and FeOS 3 pseudotetrahedra), in contrast to the centrosymmetric, nonpolar structures of La 2 O 2 Fe 2 OQ 2 (I4/mmm symmetry) with slower kinetics. It is not clear whether a dipole across the photoactive cation or a polar axis in the crystal structure would have the greater effect of enhancing e − −h + separation.…”
Section: Discussionmentioning
confidence: 93%
“…The spike observed in the transient photocurrent response for CaFeSeO indicates fast carrier generation (e – –h + separation), then the establishment of a steady state with a balance between transfer and recombination phenomena, notably at the surface of the sample (Figure ). It has been shown that an internal field due to a polar crystal structure (e.g., in ferroelectrics) minimizes charge carrier recombination and instead favors transfer at the interfaces . Both CaFeSeO and CaFeSO samples studied in this work adopt polar crystal structures (of Cmc 2 1 and P 6 3 mc symmetries, respectively) , and are composed of polar units (FeO 2 Se 2 and FeOS 3 pseudotetrahedra), in contrast to the centrosymmetric, nonpolar structures of La 2 O 2 Fe 2 O Q 2 ( I 4/ mmm symmetry) with slower kinetics.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, ferroelectrics can form spontaneous dipole moments without an applied force. [31] The unique piezopotential and polarization charges provide great opportunities to efficaciously separate and migrate carriers, endowing piezoelectric materials with great photo/ electrocatalytic potential. Several representatives of piezoelectric materials, such as piezoelectric semiconductors (ZnO, MoS 2 , MoSe 2 ) and ferroelectric materials (BaTiO 3 , BiOIO 3 , lead zirconate titanate (PZT), polyvinylidene fluoride (PVDF), PbTiO 3 ), have been demonstrated to be efficient catalysts for energy and environmental reactions.…”
Section: Internal Electric Field In Piezoelectricsmentioning
confidence: 99%
“…Therefore, alternative materials are being studied recently to overcome the existing limitations, wherein perovskite semiconductors, such as BaTiO 3 , LiNbO 3 , and BiFeO 3 , are getting much attention, thanks to their appropriate bandgap for UV to visible light sensitization 8 , 9 . Among these, ferroelectric materials are reported to have more potential in photovoltaic activity in relation with the production of photoexcited charge carriers that can generate a polarization-induced electric field which induces dispersion of these photogenerated charge carriers 10 . Bismuth ferrite (BiFO 3 ) with a narrow bandgap of 2.68 eV is considered as a high-performance light catalyst with a unique twisted rhombohedral perovskite structure.…”
Section: Introductionmentioning
confidence: 99%